Adsorption of Sodium in an Aqueous Solution in Activated Date Pits - Zakaria Rahal; Abderrahmane Khechekhouche; Ayoub Barkat; Smolyanichenko Alla Sergeevna; Chekima Hamza (Universitas Pendidikan Indonesia, 2023)
The use of acid-activated local date pits from Algeria's Oued Souf region for reducing water salinity by removing sodium. The raw and activated date pits were characterized using XRD, FTIR, SEM, and BET. The study used these materials to adsorb sodium from aqueous water, with the effects of activation time, initial sodium concentration, adsorption time, and pH of the solution on sodium removal being investigated. The specific surface area of natural date pits was found to be 645.46 m2/g, while activated date pits had a maximum of 825.03 m2/g. The maximum sodium adsorption capacity was observed at an adsorption time of 90 min, Na+ concentration of 600 mg/L, solution pH of 9.0, and adsorbent dosage of 0.1 g. The equilibrium data obtained from the experiment were analyzed using Langmuir and Freundlich isotherm models. The findings revealed that among the isotherm models examined, the Freundlich isotherm model demonstrated the strongest fit, exhibiting a high correlation coefficient of 0.999. Furthermore, the adsorption kinetics were investigated through the analysis of the pseudo-first-order and pseudo-second-order models, and the results indicated that the pseudo-second-order model provided the most suitable fit, with a correlation coefficient of 0.996.